Meio biótico nos estudos de impacto ambiental em Minas Gerais - uma abordagem faunística - Colen, Daniel Sampaio (2018)
The review of the quality of the environmental impact studies has been pointed out as an important element of the Environmental Impact Assessment process performance appraisal, with a predominance of checklists, adapted to the context of the research in which it is intended to be developed. Thus, this study’s objective was to evaluate the quality of the studies on the faunistic biotic environment within the scope of the Environmental Impact Studies (EIS) approved by the Superintendência Regional de Meio Ambiente – SURPRAM (Regional Environmental Authority) of the East of Minas Gerais from 2000 to 2015. For this purpose, using structured checklists with technical and legal variables, data were collected from 48 EIS of enterprises in the mining, industrial, energy, urban and transportation sectors. The analyzes were carried out based on 7 legal variables contained in the Resolução CONAMA 01/1986 and in the FEAM Terms of Reference and by means of 15 technical-scientific parameters described in the specialized literature. The results pointed to EIS, predominantly with "high to very high" qualities of legal agreement and "very low to medium" quality of technical agreement, besides indicating the main flaws contained in the studies, such as the methodology used in the fauna inventories, the length of field work, the insufficient sampling effort, the lack of seasonality, the absence of statistical analysis and the reduced number of specialists involved in the survey work. Therefore, what was observed was the compliance with the legislation and the disregard for the technical criteria recommended for a good faunistic biotic environment study. The analyzes carried out in this study served as indicators on the general state of EIS effectiveness approved by the environmental agency, regarding the faunal diagnosis, and can be useful in the process of impact evaluation in the state of Minas Gerais.